0,5×x_2/3×x=5/12
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
0,5.x-2/3.x=5/12
(0,5-2/3).x =5/12
(-1/6).x =5/12
x =5/12:(-1/6)
x =-5/2
Vậy x=-5/2
a,3/4 . (-5/12)+3/4.(-7/12)
` 3/4 . [ - ( 5/12 + 7/12 ) ] `
`3/4 . (-1) = -3/4 `
`2/3 . x - 0,5 = 3/4 `
` x - 0,5 = 3/4 - 2/3 `
` x-0,5 = 1/12 `
` x = 1/12 + 0,5 `
` x= 7/12 `
Bài 2:
a: =>2/3x=3/4+1/2=3/4+2/4=5/4
=>x=5/4:2/3=5/4*3/2=15/8
b:=>-2x+4=3x-12
=>-5x=-16
=>x=16/5
Pt \(\Leftrightarrow\dfrac{1}{2}x-\dfrac{2}{3}x=\dfrac{5}{12}\)
\(\Leftrightarrow x\left(\dfrac{1}{2}-\dfrac{2}{3}\right)=\dfrac{5}{12}\)
\(\Leftrightarrow-\dfrac{1}{6}.x=\dfrac{5}{12}\)
\(\Leftrightarrow x=-\dfrac{5}{2}\)
0,5.x-\(\dfrac{2}{3}\).x=\(\dfrac{5}{12}\)
\(\Leftrightarrow\)\(\dfrac{1}{2}\).x-\(\dfrac{2}{3}\).x=\(\dfrac{5}{12}\)
\(\Leftrightarrow\)x.(\(\dfrac{1}{2}\)-\(\dfrac{2}{3}\))=\(\dfrac{5}{12}\)
\(\Leftrightarrow\)x.\(\dfrac{-1}{6}\) =\(\dfrac{5}{12}\)
\(\Leftrightarrow\)x =\(\dfrac{5}{12}\):\(\dfrac{-1}{6}\)
\(\Leftrightarrow\)x =\(\dfrac{5}{12}\).\(\dfrac{-6}{1}\)
\(\Leftrightarrow\)x = \(\dfrac{-5}{2}\)
a: \(\left\{{}\begin{matrix}x_1+x_2=-b\\x_1x_2=c\end{matrix}\right.\Leftrightarrow\left\{{}\begin{matrix}b=10\\c=-24\end{matrix}\right.\)
b: \(\left\{{}\begin{matrix}x_1+x_2=-b\\x_1x_2=c\end{matrix}\right.\Leftrightarrow\left\{{}\begin{matrix}-b=-5\\c=0\end{matrix}\right.\Leftrightarrow\left\{{}\begin{matrix}b=5\\c=0\end{matrix}\right.\)
c: \(\left\{{}\begin{matrix}x_1+x_2=2\\x_1x_2=1-2=-1\end{matrix}\right.\Leftrightarrow\left\{{}\begin{matrix}b=-2\\c=-1\end{matrix}\right.\)
d: \(\left\{{}\begin{matrix}x_1+x_2=3-\dfrac{1}{2}=\dfrac{5}{2}\\x_1x_2=-\dfrac{3}{2}\end{matrix}\right.\Leftrightarrow\left\{{}\begin{matrix}b=-\dfrac{5}{2}\\c=-\dfrac{3}{2}\end{matrix}\right.\)
b. \(\dfrac{45}{100}:3-\dfrac{24,5}{100}:5\)
=\(0,45:3-0,245:5\)
= 0,15 - 0,049
= 0,101
c. 0,56 - \(\dfrac{12}{100}\)+ \(\dfrac{3}{4}-1\)
= 0,56 - 0,12 + 0,75 - 1
= 0,19
d. ( 0,4 x 7 - \(\dfrac{140}{100}\):0,5) x \(\left(\dfrac{2}{100}+\dfrac{4}{100}+\dfrac{6}{100}+...+1\right)\)
= (2,8 - 2,8 ) x (0,02 + 0,04 +0,06 +...+1)
=0